Hubungan Usia Kronologis Awal Masuk Sekolah dengan Prestasi Belajar Siswa Sekolah Dasar - Assyifa Fauzia; Deswalantri Deswalantri (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research was conducted based on the problem that it was found that there were still students who were enrolled in school at the age that had been determined by the government (seven years). The result of an interviwe with the parik putuih integrated Islamic Elemtery School teacher stated that there were students who entered school in 2016 who were under the age of seven. This study aims to see whether on variable has a relationship with other variables. Data collection wascarried out using the documentation method to see the chronological age at the beginning of school entry and semester I and II grades from grade 1 to grade 3 elementary shool. This study uses data analysis spearman Rank Correlation (Grade Correlation). The results obtained using the Spearman Rank Correlation technique otained hit 0,352 and tab at a significant level of 5% is 0.364. It is proven that there is no relationship between crhonological age at the beginning of school and student achievement. The result show that H_0 is accept and H_a is rejected. So it can be concluded that the level of relationship between crhonological age at the beginning of school entry and student achievement at SDIT Baiturrahim Parik Putuih Kabupaten Agam is at a low level or there is not relationship.